Insights from the design and implementation of a single-entry model of referral for total joint replacement surgery: Critical success factors and unanticipated consequences. Issue 2 (February 2018) - Damani, Zaheed; MacKean, Gail; Bohm, Eric; Noseworthy, Tom; Wang, Jenney Meng Han; DeMone, Brie; Wright, Brock; Marshall, Deborah A.
Highlights: The Winnipeg Central Intake Service (WCIS) employs single-entry, centralized intake and triage. The WCIS streamlined processes; improved referrals, patient care, and monitoring of outcomes. Challenges included low initial understanding, participation, and slow uptake. Unanticipated consequences included incorrect perceptions, increased referral volume, incomplete information sharing. Recommendations for successful implementation: early communication, clear processes, physician leadership, greater patience. Abstract: Background: Single-entry models (SEMs) in healthcare allow patients to see the next-available provider and have been shown to improve waiting times, access and patient flow for preference-sensitive, scheduled services. The Winnipeg Central Intake Service (WCIS) for hip and knee replacement surgery was implemented to improve access in the Winnipeg Regional Health Authority. This paper describes the system's design/implementation; successes, challenges, and unanticipated consequences. Methods: On two occasions, during and following implementation, we interviewed all members of the WCIS project team, including processing engineers, waiting list coordinators, administrators and policy-makers regarding their experiences. We used semi-structured telephone interviews to collect data and qualitative thematic analysis to analyze and interpret the findings. Results: Respondents indicated that the overarching objectives of the WCIS were being met. Benefits included streamlined processes, greater patient access, improved measurement and monitoring of outcomes. Challenges included low awareness, change readiness, and initial participation among stakeholders. Unanticipated consequences included workload increases, confusion around stakeholder expectations and under-reporting of data by surgeons' offices. Critical success factors for implementation included a requirement for clear communication, robust data collection, physician leadership and patience by all, especially implementation teams. Conclusions: Although successfully implemented, key lessons and critical success factors were learned related to change management, which if considered and applied, can reduce unanticipated consequences, improve uptake and benefit new models of care.